2016
DOI: 10.1016/j.jaad.2016.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Adult female acne and associated risk factors: Results of a multicenter case-control study in Italy

Abstract: Lifestyle factors may play an important role for acne development in adulthood, but their role should be further assessed in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
53
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 19 publications
10
53
1
11
Order By: Relevance
“…A recent case-control study reported the presence of hirsutism in 17.4% of 248 women with acne (significantly higher rates compared to 3.7% in controls, P < 0.001), similarly to our results. 7 Polycystic ovary syndrome was found in 19% of adult women with acne in our study. The presence of PCOS in adult acne patients has been evaluated in a limited number of studies 7,10,11 reporting statistically significant higher rates of PCOS in females with acne compared to controls; 26.9% of 52 patients 18-35 years old, 10 37.3% of 51 patients 15-46 years old, 12 or 27.2% of 248 adult patients 7 ( Table 2).…”
supporting
confidence: 50%
See 1 more Smart Citation
“…A recent case-control study reported the presence of hirsutism in 17.4% of 248 women with acne (significantly higher rates compared to 3.7% in controls, P < 0.001), similarly to our results. 7 Polycystic ovary syndrome was found in 19% of adult women with acne in our study. The presence of PCOS in adult acne patients has been evaluated in a limited number of studies 7,10,11 reporting statistically significant higher rates of PCOS in females with acne compared to controls; 26.9% of 52 patients 18-35 years old, 10 37.3% of 51 patients 15-46 years old, 12 or 27.2% of 248 adult patients 7 ( Table 2).…”
supporting
confidence: 50%
“…3 A dramatic improvement of the skin appearance on the application site of imiquimod has been observed in patients with XP. [2][3][4][5][6][7] We report two children with XP treated with imiquimod 5% cream, establishing a chemoprophylaxis for cancerization field. Patient 1: A diagnosis of XP was established in a 5-yearold boy with a BCC on his eyelid and multiple hyperpigmented macules on his face (Fig.…”
mentioning
confidence: 99%
“…2). Two case-control studies were excluded from the meta-analysis due to study design, but their results were still in line with the observed trend in the meta-analysis 11,25 . In addition, a study seems to suggest a possible additive effect of maternal Continued and paternal family history on the prevalence of acne, as a larger odds ratio of 2.6 is observed if both parents have acne, compared to an odds ratio of 2.1 and 1.7 for maternal and paternal acne, respectively 26 .…”
Section: Genetic and Hormonal Factors That Influence Acne Presentatiomentioning
confidence: 64%
“…Several level C papers reported that a low intake of fruits or vegetables triggers acne, especially in the female population, while the Mediterranean diet, rich of vegetables and fruits and unsaturated fatty acids, positively impacts acne …”
Section: Resultsmentioning
confidence: 99%
“…99 Several level C papers reported that a low intake of fruits or vegetables triggers acne, especially in the female population, while the Mediterranean diet, rich of vegetables and fruits and unsaturated fatty acids, positively impacts acne. 100,101 Nutrition and potential targets in acne Keratinocytes Abnormal follicular keratinization is important for comedone formation in acne. Diet-induced changes in sebum quantity and composition may not only induce the inflammation of acne but may also drive the process of comedogenesis.…”
Section: Nutrients Which Are Potentially Beneficial In Acnementioning
confidence: 99%